2015
DOI: 10.1523/jneurosci.0614-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Periphery for a Subsequent Behavior: Motor Neuronal Activity during Biting Generates Little Force but Prepares a Retractor Muscle to Generate Larger Forces during Swallowing inAplysia

Abstract: Some behaviors occur in obligatory sequence, such as reaching before grasping an object. Can the earlier behavior serve to prepare the musculature for the later behavior? If it does, what is the underlying neural mechanism of the preparation? To address this question, we examined two feeding behaviors in the marine mollusk Aplysia californica, one of which must precede the second: biting and swallowing. Biting is an attempt to grasp food. When that attempt is successful, the animal immediately switches to swal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…As a first step toward locating the bursts of identified motor neurons and their firing frequencies, individual spikes were detected and grouped into spike trains using manually specified window discriminators, which captured signal peaks on a given channel occurring within a given amplitude range and time window. Individual motor neurons can be identified from extracellular nerve signals in this system because of their reliable relative amplitudes and phase of activity (Morton and Chiel, 1993b;Lu et al, 2013Lu et al, , 2015McManus et al, 2014;Cullins et al, 2015b) (see Table 1). The spike amplitude of some neurons, especially B8a/b and B4/B5, can vary when these neurons activate at high frequencies due to spike collisions seen in the extracellular nerve recordings (Morton and Chiel, 1993b;Warman and Chiel, 1995), so we designed the window discriminators to account for this variability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As a first step toward locating the bursts of identified motor neurons and their firing frequencies, individual spikes were detected and grouped into spike trains using manually specified window discriminators, which captured signal peaks on a given channel occurring within a given amplitude range and time window. Individual motor neurons can be identified from extracellular nerve signals in this system because of their reliable relative amplitudes and phase of activity (Morton and Chiel, 1993b;Lu et al, 2013Lu et al, , 2015McManus et al, 2014;Cullins et al, 2015b) (see Table 1). The spike amplitude of some neurons, especially B8a/b and B4/B5, can vary when these neurons activate at high frequencies due to spike collisions seen in the extracellular nerve recordings (Morton and Chiel, 1993b;Warman and Chiel, 1995), so we designed the window discriminators to account for this variability.…”
Section: Discussionmentioning
confidence: 99%
“…Burst identification using frequency thresholds. Previous work has shown that muscles in this system act as low-pass filters, and motor neuron activity may not result in measurable force if firing rates are too slow or activity is too brief (Yu et al, 1999;Lu et al, 2015). To address this, frequency thresholds were applied to the spike trains identified in the previous step to determine the start and end of candidate bursts (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One working hypothesis to still explore is that by such attenuation the 'scene' (i.e., the body environment) is prepared/made ready/transformed into the scene for something else. For example, nature is rife with examples of processes which were once thought of as irrelevant, and which have proved to be meaningful (e.g., the aplysia biting or swallowing muscles; Lu, Mcmanus, Cullins, & Chiel, 2015).…”
Section: A Reconsideration Of Tactile Suppressionmentioning
confidence: 99%